Estimation of Flexural Strength of Plain Concrete from Ultrasonic Pulse Velocity - Ala’a Hussein. Alwan Al-Zuhairi (Journal of Engineering, 2023)
The aim of this study is to propose mathematical expressions for estimation of the flexural strength of plain concrete members from ultrasonic pulse velocity (UPV) measurements. More than two hundred pieces of precast concrete kerb units were subjected to a scheduled test program. The tests were divided into two categories; non-destructive ultrasonic and bending or rupture tests. For each precast unit, direct and indirect (surface) ultrasonic pulses were subjected to the concrete media to measure their travel velocities. The results of the tests were mointered in two graphs so that two mathematical relationships can be drawn. Direct pulse velocity versus the flexural strength was given in the first relationship while the second equation describes the flexural strength as a function of indirect (surface) pulse velocity. The application of these equations may be extended to cover the assessment of flexural strength of constructed concrete kerb units or in-situ concreting kerbstone and any other precast concrete units. Finally, a relation between direct and indirect pulse velocities of the a given concrete was predicted and suggested to be employed in case when one of the velocities is not available can be measured for other ultrasonic pulse test applications